2008
DOI: 10.1097/01.tp.0000296060.39823.a4
|View full text |Cite
|
Sign up to set email alerts
|

Innervation and Secretory Function of Transplanted Human Submandibular Salivary Glands

Abstract: Free submandibular gland autotransplantation is used to treat absolute tear deficiency. Although disconnected from any peripheral innervation, most transplants show increasing secretion for years. We have evaluated the secretory activity and autonomic innervation of such transplants. Secretory activity of glands in response to parasympatholytics and parasympathomimetics was evaluated by Schirmer's test and Technetium scintigraphy. Submandibular gland tissue specimens taken before and after transplantation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
(25 reference statements)
1
40
1
Order By: Relevance
“…Over the subsequent months the amount of secretion increases. Contrary to short-term reports by others, after 1 year this can result in excessive salivary epiphora [4,20,26,30]. Although the secretory flow does not depend on gustatory stimuli, it is stimulated by physical activity, local hyperthermia or caffeine ingestion.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Over the subsequent months the amount of secretion increases. Contrary to short-term reports by others, after 1 year this can result in excessive salivary epiphora [4,20,26,30]. Although the secretory flow does not depend on gustatory stimuli, it is stimulated by physical activity, local hyperthermia or caffeine ingestion.…”
Section: Resultscontrasting
confidence: 52%
“…Adrenergic axons are also present in the glands but are less numerous than normal and more irregularly distributed. The latter are thought to have originated from sectioned sympathetic nerves around reconnecting arteries and to have grown by sprouting down mainly formerly parasympathetic glandular nerves [30].…”
Section: Resultsmentioning
confidence: 99%
“…16 This indicates that sympathetic activation affects the secretory activity of the transplanted SMG. Geerling et al 12 observed irregularly distributed adrenergic axons in the transplanted SMG. In addition to autonomic nerves, secretion-related receptors on the cell membrane, such as TRPV1, and tight junctions also play an important role in regulating secretion from normal and transplanted SMGs.…”
Section: Discussionmentioning
confidence: 98%
“…The hypersensitive mAChRs would then induce AQP5 trafficking out of lipid rafts, resulting in excessive gland secretion. 11 Geerling et al 12 demonstrated the distribution of autonomic nerve endings in transplanted SMGs in the long term. These fundamental research studies indicate the possibility of reinnervation of the transplanted glands.…”
mentioning
confidence: 98%
“…Similarly distributed ganglia were also observed in the stroma of the human MGl (Geerling et al 2008;Tosios et al 2010). In humans, the small ganglia were observed to be in close association with salivary parenchymal cells and blood vessels.…”
Section: Discussionmentioning
confidence: 88%